Survey on Management of Spotted Pod Borer (Maruca vitrata Fabricius) on Yardlong Bean in Chitwan, Nepal - Regmi, Rajendra.; Tiwari, Sundar; Thapa, Resham Bhadur; Maharjan, Ranju; poudel, Sujata poudel; Poudel, Kapil Poudel (International Journal of Applied Sciences and Biotechnology, 2016)
A household survey was conducted during January 2012 in Gunjanagar, Dibyanagar and Sukranagar Village Development Committee of Chitwan district to know the socioeconomic status, status of spotted pod borer and its management practice. The survey included purposive random sampling methods in 35 yardlong bean growers. Most of commercial farmers have been growing since 3-7 years. Nearly three fourth of the farmers considered spotted pod borer as a major pest of yarldlong bean in Chitwan. Most of them considered more than 60% loss caused by spotted pod borer if no management practice is applied. Almost all sprayed chemical pesticides for management of spotted pod borer and nearly three fourth of them used more than one chemical pesticides alternately for management of spotted pod borer.One third farmers (31.43%) applied chemical pesticides in 4-7 days interval and one third of them (31.43%) applied chemical pesticides in 7-10 days interval after beginning of flowering for management of spotted pod borer. Almost all farmers (94.29%) knew adverse effect of pesticides on human, environment, natural enemies and other animal. Majority (94.29%) of farmers harvested pods after 1-3 day of spray of chemical pesticides and very few (14.29%) of commercial grower of this area get training in insect pest management.Int J Appl Sci Biotechnol, Vol 4(1): 39-43